Investigation of Lubricant Oil Film Thickness on Workpiece under Minimum Quantity Lubrication Milling Process - Nurrina, Rosli; Nur Izzati Khoirunnisa, Ismail; Amiril Sahab, Abdul Sani; Afifah Nailah, Muhamad (J-Global, 2023)
Minimum Quantity Lubrication (MQL) technology has drawn attention as an effective lubrication technique despite its small usage of lubricants during the machining process. The technology has undeniably minimized the manufacturing cost as well as the adverse impacts towards the environment and health of operators. However, the ability of the small droplets of lubricant oil to penetrate the cutting zone must be investigated to enhance the machining performance. The penetration ability can be predicted if the amount of lubricant oil adhered to the workpiece is known. Nonetheless, observing the lubricant behavior is commonly challenged by the existing tools during the machining process. Therefore, a non-intrusive technique must be applied to conscientiously observe the lubricant behavior. In this paper, the thickness of lubricant oil resulted by the droplets accumulation on the workpiece during MQL milling process was measured using a Laser-Induced Fluorescence technique to predict the lubricating effects of the lubricant. The surface roughness of workpiece was also measured to investigate how the thickness of lubricant oil affects the machining performance. Experiments were conducted for MQL milling process of aluminium alloy 6061 under constant value of cutting speed and increasing value of lubricant flow rates. The MQL nozzle was tilted 45°, directed perpendicular to the milling direction and fixed together with the cutting tool to let them move together throughout the milling path. Results analysis was performed on the sample whose cutting tool was halfway to the milling path. As a result, the average lubricant oil film thickness was found to increase and obviously fluctuate with increasing flow rates, ranging from 0.2 mm to 0.7 mm. A careful observation of the lubricant oil thickness near the location of cutting tool also suggested that the droplets of lubricant oil probably struggle to penetrate the cutting zone due to the sudden falls at those locations. Furthermore, the correlation between the thickness of lubricant oil film to the performance of milling process under the MQL spraying condition was successfully made since the results trending of the surface roughness of workpiece shows a well agreement with the trending of lubricant oil film thickness.